“Avantivarman: Development of Irrigation and Agriculture during Avantivarman’s Rule in Kashmir” - Javeed Ahmad Mir (Innovative Research Thoughts, 2018)
Avantiverman (853-888 A.D.) belonged to Utpala dynasty emerged as a powerful King. He was most sagacious king. He built temples at Avantipur after his name. His Minister Suyya was a great genius. His court had a pride on two poets-Ranakar and Ananvardhana. During his time price of paddy showed a deep decline from 36 to 20 dinars. Suyya who was a great engineer is said to have drained a large chunck of wasteland during his regime. His memory is commemorated by Suyyapur or Sopore, a township in Baramulla district. It is said that when this great engineer was working in Sopore no people were coming forth to plunge themselves in gushing water. The king thereupon ordered that a part of treasury may be thrown into the water, a large number of people plunged into the river to get as many coins as they could. The skill of Suyya worked and the river was cleared of silt. Sopore town in Baramulla district of Jammu and Kashmir was founded by the famous Utpala engineer and irrigation minister Suyya during the peaceful reign of king Avantivarman in 880 CE.